(untitled) (Canadian Eye Care Today, 2025)
Elevated intraocular pressure (IOP) and glaucomatous optic neuropathy are common complications in patients with uveitis. Ocular hypertension occurs in approximately 25% of uveitic patients. In addition, retrospective observational studies have found that 31-77% of patients with ocular hypertension had converted to glaucomatous optic neuropathy over a 10 year period. Ocular hypertension occurs in approximately 35% of children with uveitis, with secondary glaucoma occurring in 11-38%. Many of these children will require surgical glaucoma interventions: 11.5% at 1 year after a diagnosis of ocular hypertension, increasing to 50% by 5 years. In adults with non-infectious uveitis, the rate of surgical glaucoma interventions is between 20-40%.